LncRNA NONHSAT042241 inhibits rheumatoid synovial proliferation, inflammation and aggression via inactivating WNT/β-catenin signaling pathway - Yehua Jin; Cen Chang; Xinpeng Zhou; Runrun Zhang; Ping Jiang; Kai Wei; Linshuai Xu; Yiming Shi; Guizhen Yang; Xinliang Lv; Yuejuan Zheng; Dongyi He (Taylor & Francis Group, 2024)
Objective This study aims to explore the effect of NONHSAT042241 on the function of rheumatoid arthritis -fibroblast-like synoviocyte (RA-FLS) and the underlying mechanisms.Methods RA-FLS was treated with NONHSAT042241 overexpression and NONHSAT042241 knockdown lentiviruses. Cell counting kit-8 (CCK-8) assay, colony formation assay, flow cytometry, Transwell assay, western-blot, ELISA, and qRT-PCR were used to measure the changes of cell proliferation, apoptosis, invasion, secretion of inflammatory cytokines and matrix metalloproteinases (MMPs). Fluorescent in situ hybridization (FISH) assay, RNA pull-down assay, mass spectrometry (MS) and RNA immunoprecipitation (RIP) were used to find the target proteins that bond to NONHSAT042241, and western-blot was used to detect the expression of related proteins of Wnt/β-catenin signaling pathway.Results Overexpression of NONHSAT042241 inhibited the proliferation of RA-FLS (p < 0.05), invasion, secretion of pro-inflammatory factors (IL-1and IL-6) and MMPs (MMP-1 and MMP-3) (p < 0.05), and elevated the level of pro-apoptotic factors (Bax and cleaved caspase3), while NONHSAT042241 knockdown had the opposite effect. NONHSAT042241 can directly bind to hnRNP D, and down-regulated the expression of β-catenin (p < 0.05), p-GSK-3β (p < 0.05), Cyclin D1 (p < 0.05), PCNA (p < 0.05), and thus reduced the cell proliferation.Conclusion NONHSAT042241 may inhibit FLS-mediated rheumatoid synovial proliferation, inflammation and aggression. The underlying mechanisms may be that NONHSAT042241 inhibits the activity of Wnt/β-catenin signaling.